Processive Recoding and Metazoan Evolution of Selenoprotein P: Up to 132 UGAs in Molluscs - Baclaocos, Janinah; Santesmasses, Didac; Mariotti, Marco; Bierla, Katarzyna; Vetick, Michael; Lynch, Sharon; Mcallen, Rob; Mackrill, John; Loughran, Gary; Guigó, Roderic; Szpunar, Joanna; Copeland, Paul; et al. (Journal of Molecular Biology, 2019)
International audience Selenoproteins typically contain a single selenocysteine, the 21st amino acid, encoded by a context-redefined UGA. However, human selenoprotein P (SelenoP) has a redox-functioning selenocysteine in its N-terminal domain and nine selenium transporter-functioning selenocysteines in its C-terminal domain. Here we show that diverse SelenoP genes are present across metazoa with highly variable numbers of Sec-UGAs, ranging from a single UGA in certain insects, to 9 in common spider, and up to 132 in bivalve molluscs. SelenoP genes were shaped by a dynamic evolutionary process linked to selenium usage. Gene evolution featured modular expansions of an ancestral multi-Sec domain, which led to particularly Sec-rich SelenoP proteins in many aquatic organisms. We focused on molluscs, and chose Pacific oyster Magallana gigas as experimental model. We show that oyster SelenoP mRNA with 46 UGAs is translated full-length in vivo. Ribosome profiling indicates that selenocysteine specification occurs with ~5% efficiency at UGA1 and approaches 100% efficiency at distal 3' UGAs. We report genetic elements relevant to its expression, including a leader open reading frame and an RNA structure overlapping the initiation codon that modulates ribosome progression in a seleniumdependent manner. Unlike their mammalian counterparts, the two SECIS elements in oyster SelenoP (3'UTR recoding elements) do not show functional differentiation in vitro. Oysters can increase their tissue selenium level up to 50-fold upon supplementation, which also results in extensive changes in selenoprotein expression.